Pengaruh Tingkat Keberhasilan Usaha Penggilingan Gabah di Kabupaten Sidrap yang Dipengaruhi oleh Pengaruh Pengetahuan Kewirausahaan - Nurliani; Kurniawan Husain, Tsalis; Rosada, Ida; Riskiah, Suci (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
Sidrap Regency is a rice production center in South Sulawesi. The abundant rice production impacts the increase in the rice milling industry and the community's economic growth. Government policy aims to protect farmers by maintaining high rice prices, but on the other hand, it must protect farmers by maintaining high rice prices. On the other hand, it must protect consumers by lowering rice prices. Entrepreneurial knowledge is an important variable in studying its influence on business success. This study aims to describe the entrepreneurial knowledge of rice milling managers in Sidrap Regency, describe the level of success of rice milling businesses, and analyze the effect of entrepreneurial knowledge on the success of rice milling businesses. The survey was conducted using the saturated sampling method on 32 rice milling business units. Quantitative descriptive and multiple regression analyses were used to test the research hypothesis. The results showed that entrepreneurial knowledge scored 1,065, meaning that rice milling business managers have knowledge of business, roles, responsibilities, personality, self-ability, management, and organization. In addition, the level of success of rice milling businesses scored 403, including the flourishing category. It showed increased sales volume, business profits, and labor utilization. The entrepreneurial knowledge variable also has a significant and positive influence on the success of the rice milling business.